Rectal Cancer - Staging and Surgical Approach - Manousos-Georgios, Pramateftakis; Vasileios, Papadopoulos; Antonios, Michalopoulos; Konstantinos, Spanos; Konstantinos, Tepetes; Georgios, Tsoulfas (IntechOpen, 2012)
None